Measuring financial fragmentation in the euro area corporate bond market - Guillaume Horny; Simone Manganelli; Benoît Mojon (Journal of Risk and Financial Management, 2018)
This paper analyses the determinants of euro area non-financial corporate bonds since the early 2000s, so as to gauge deviations from the law of one price. We decompose the spread between the yield of German, French, Italian and Spanish corporate bonds vis-à-vis the German Bund of similar maturity into country, credit and duration risk premia components via dummy regressions. We highlight three main findings. First, the initial phase of the financial crisis (2008-2009) caused an overall increase in credit risk premia. Since the beginning of 2013 credit risk premia are back to levels comparable to those preceding the financial crisis. Second, at the height of the euro area sovereign crisis (2011-2012), high credit risk premia were accompanied by strong and persistent signs of market fragmentation in Italy and Spain (but not in France). This fragmentation has reached its peak in the second half of 2012 and has started to recede only after the announcement of the OMT. Third, we provide a simple measure of financial integration across the big 4 member states of the euro area.
Keywords: E43; G12; G24; C23; 330; financial integration; credit risk; country premia; fragmentation index